The Dose Window for Radiation-Induced Protective Adaptive Responses - Ronald E. J. Mitchel (SAGE Publishing, 2010)
Adaptive responses to low doses of low LET radiation occur in all organisms thus far examined, from single cell lower eukaryotes to mammals. These responses reduce the deleterious consequences of DNA damaging events, including radiation-induced or spontaneous cancer and non-cancer diseases in mice. The adaptive response in mammalian cells and mammals operates within a certain window that can be defined by upper and lower dose thresholds, typically between about 1 and 100 mGy for a single low dose rate exposure. However, these thresholds for protection are not a fixed function of total dose, but also vary with dose rate, additional radiation or non-radiation stressors, tissue type and p53 functional status. Exposures above the upper threshold are generally detrimental, while exposures below the lower threshold may or may not increase either cancer or non-cancer disease risk.